Hydraulic geometric optimization on stagnating flow at the inlet of main pipe of underground pumping station. Issue 1 (1st September 2022) - Guo, M; Yao, K W; Zhang, S H
Abstract: The underground pumping station is widely used in many important fields. However, the stagnating flow caused by the sharp geometric gradient at the interface between the primary pump intake and the main pipeline not only causes the performance deteriorations of the whole pump station but also leads to safety and operational stability challenges. In this paper, the numerical model of the related hydraulic phenomena is presented, moreover, the effectiveness and accuracy of the numerical model are verified by comparing it with the experimental results. The simulation results indicate that the hydraulic geometry optimization scheme at the inlet of the main pipe with 0.10 D (inner diameter of the main pipe) local rounding contributes the best effect on the hydraulic efficiency and operation stability of underground pump stations. The results may give a reference for the design of underground pump stations and the optimization of hydraulic geometry in related fields.